Body Mass Index and Waist Circumference are Associated with Visceral Fats Measured by Bioelectrical Impedance Analysis in Adolescents - Darmawati Ayu Indraswari; Hafizhil Uzhma Al Ahmadi; Devi Wahyu Arum Sari; Timothy Jordan; Buwono Puruhito; Edwin Basyar; Saekhol Bakri; Muflihatul Muniroh (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2021)
Background: Overweight and obesity are two health conditions that contribute to the impaired quality of life. Two parameters of obesity also indicating body composition, body mass index (BMI) and waist circumference (WC), have been used as simple tools to assess abdominal visceral fats. The correlation between both measurements and visceral fats remains unclear.Objective: The study aims at demonstrating that body mass index and waist circumference may reflect visceral fats using bioelectrical impedance analysis in adolescents.Methods: First-year students of the Faculty of Medicine Diponegoro University participated in the study. This cross-sectional study measured BMI, WC, mid-arm circumference (MAC), and visceral fat (VF) of 130 participants. BMI, WC, MAC, and VF were assessed using Omron digital scale, measuring tape, and body impedance analysis, respectively. Spearman test was used for the bivariate analysis while multiple regression was employed to perform multivariate analysis. Significant results were determined if p value <0.05 for the bivariates.Results: The correlation between body mass index and visceral fats showed a strong value with r: 0.794 and p-value=<0.001. The correlation between mid-arm circumference and visceral fats showed r= 0.713 and p value=<0.001. Meanwhile the correlation between waist circumference and visceral fats showed r= 0.655 and p value=<0.001. BMI and WC showed the greatest correlation to VF. The comparison between genders resulted in men having stronger relationships between BMI and VF, and WC and VF.Conclusion: BMI and waist circumference are strongly related to visceral fats based on BIA in medical students.